2012
DOI: 10.1002/hep.25738
|View full text |Cite
|
Sign up to set email alerts
|

Efficient replication of primary or culture hepatitis C virus isolates in human liver slices: A relevantex vivomodel of liver infection

Abstract: The development of human cultured hepatitis C virus (HCV) replication-permissive hepatocarcinoma cell lines has provided important new virological tools to study the mechanisms of HCV infection; however, this experimental model remains distantly related to physiological and pathological conditions. Here, we report the development of a new ex vivo model using human adult liver slices culture, demonstrating, for the first time, the ability of primary isolates to undergo de novo viral replication with the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…A limitation of this study is still that this model is restricted to cell culture-derived viruses and it is unclear if also patient-derived viruses can be propagated in this system. A very recent study which is based on ex vivo human adult liver slices demonstrated a productive infection using human primary isolates of genotype 1b as well as JFH1 viruses and genotype 1 JFH1 chimeric genomes (Lagaye, Shen et al 2012). This new experimental model system in which viral titers above 10 5 ffu/ml were achieved allows in addition the validation of antiviral drugs.…”
Section: Hcv Replication Models In Primary Cells and Patient Isolatesmentioning
confidence: 90%
“…A limitation of this study is still that this model is restricted to cell culture-derived viruses and it is unclear if also patient-derived viruses can be propagated in this system. A very recent study which is based on ex vivo human adult liver slices demonstrated a productive infection using human primary isolates of genotype 1b as well as JFH1 viruses and genotype 1 JFH1 chimeric genomes (Lagaye, Shen et al 2012). This new experimental model system in which viral titers above 10 5 ffu/ml were achieved allows in addition the validation of antiviral drugs.…”
Section: Hcv Replication Models In Primary Cells and Patient Isolatesmentioning
confidence: 90%
“…It is still unclear whether discrepancies between models [9] could not also relate to active HCV replication in a non-physiological environment [76] , differences between viral genotypes [12] and/or differential processing of some HCV proteins [58] . Nevertheless, host factors involved in BHK-WNV cells were also required in Huh-7.5 cells that, over time, developed a cytoplasmic compartment [26] enriched in HCV core, CANX and RAB1.…”
Section: Discussionmentioning
confidence: 99%
“…hepatocytes [58] . In contrast, no clear effect of the inhibitor was observed on HCV production with BHK-WNV cells …”
Section: Caspase-1 Is Required For the Release Of Hcv Particles Via Imentioning
confidence: 99%
“…Recently it was shown that HCV infection could be studied in human liver slices. 168 For the rst time, the ability of primary HCV isolates to undergo de novo viral replication in human liver slices was demonstrated. This opens up the possibility of using liver slices to study virus infections that can lead to liver brosis.…”
Section: Viral Infection Researchmentioning
confidence: 99%